Cytomegalovirus lymphadenitis mimicking a relapsed diffuse large B‐cell lymphoma. Issue 12 (26th December 2022) - Delaye, Matthieu; Ricard, Laure; Maisonobe, Lucas; Chartier, Suzanne; Coppo, Paul
Abstract: Cytomegalovirus (CMV) reactivation is frequent after autologous stem cell transplantation (ASCT), but generalized CMV lymphadenitis is rare. We report a CMV lymphadenitis after an ASCT mimicking a relapse of a diffuse large B‐cell lymphoma. After histopathological documentation, CMV lymphadenitis should be treated to avoid systemic progression. Abstract : CMV lymphadenitis is a rare complication following ASCT, which may mimic a relapse of lymphoma. Blood CMV viremia can be negative. Following histopathological documentation, CMV lymphadenitis should be treated to avoid systemic progression.